Review of Web-Based Toolkits for Health Care Practitioners Working With Women and Girls Affected by or at Risk of Female Genital Mutilation/Cutting - Hina Shaikh; Karen A. McDonnell (SAGE Publishing, 2020)
Increased migration has given rise to more advocacy efforts against female genital mutilation or cutting (FGM/C), legislation that criminalizes the practice, and guidance to the health sector for managing care of affected groups. More women and girls who have been cut or who are at risk of FGM/C are migrating from regions where it is common to countries where it is not and interacting with health professionals and other community practitioners in these host countries. Despite numerous studies on the negative health impacts of FGM/C, little is known about toolkits on FGM/C that providers can use in their prevention and response efforts. We sought to explore the nature of Internet-based products referenced as toolkits and materials characteristic of toolkits aimed at different service providers who may interact with women and girls affected by FGM/C. Through an online search, we identified 45 toolkits and collected data about each one. We found that the toolkits targeted different audiences and offered a diverse set of information and resources. The majority of toolkits were aimed at health professionals and provided factual and epidemiological-focused content, yet many did not include research evidence, skills development application, or approaches for implementing the toolkit in practice. This review is the first completed in the area of FGM/C to show a rich diversity of online materials. Future toolkits can be improved with the provision of evidence-based information and practical skills development for use by health professionals in implementing best practices in working with women and girls affected by FGM/C.